The Nutritional Potential of the Native Australian Green Plum (Buchanania obovata) Compared to Other Anacardiaceae Fruit and Nuts - Fyfe, Selina; Smyth, Heather E.; Schirra, Horst Joachim; Rychlik, Michael; Sultanbawa, Yasmina (Frontiers in Nutrition, 2020)
The native Australian green plum (Buchanania obovata) is a small fruit that grows in the northern parts of the Northern Territory and Western Australia. The fruit belongs to the family Anacardiaceae, which includes the other agriculturally important fruit mangoes, pistachios and cashew nuts. The green plum is a favoured species of fruit for the Aboriginal communities and an important bush food in the Northern Territory. To date, only minimal scientific studies have been performed on the green plum as a food. This review is about plant foods in the family Anacardiaceae and the key nutritional compounds that occur in these fruit and nuts. It looks at the more traditional nutrient profiles, some of the key health metabolites, allergens and antinutrients that occur, and the role these foods play in the health of populations. This provides a guide for future studies of the green plum to show what nutritional and anti-nutritional properties and compounds should be analysed and if there are areas where future studies should focus. This review includes an update on studies and analysis of the green plum and how its nutritional properties give it potential as a food for diet diversification in Australia.